Updated Priorities Among Effective Clinical Preventive Services - Maciosek, Michael V. (Ann Fam Med, 2017)
PURPOSE: The Patient Protection and Affordable Care Act’s provisions for first-dollar coverage of evidence-based preventive services have reduced an important barrier to receipt of preventive care. Safety-net providers, however, still serve a substantial uninsured population, and clinician and patient time remain limited in all primary care settings. As a consequence, decision makers continue to set priorities to help focus their efforts. This report updates estimates of relative health impact and cost-effectiveness for evidence-based preventive services. METHODS: We assessed the potential impact of 28 evidence-based clinical preventive services in terms of their cost-effectiveness and clinically preventable burden, as measured by quality-adjusted life years (QALYs) saved. Each service received 1 to 5 points on each of the 2 measures—cost-effectiveness and clinically preventable burden—for a total score ranging from 2 to 10. New microsimulation models were used to provide updated estimates of 12 of these services. Priorities for improving delivery rates were established by comparing the ranking with what is known of current delivery rates nationally. RESULTS: The 3 highest-ranking services, each with a total score of 10, are immunizing children, counseling to prevent tobacco initiation among youth, and tobacco-use screening and brief intervention to encourage cessation among adults. Greatest population health improvement could be obtained from increasing utilization of clinical preventive services that address tobacco use, obesity-related behaviors, and alcohol misuse, as well as colorectal cancer screening and influenza vaccinations. CONCLUSIONS: This study identifies high-priority preventive services and should help decision makers select which services to emphasize in quality-improvement initiatives.